(3fRgI GdeTJGb aj GNJQGb GdBaGbs - (3GdEOQjSj , eMeO Hf eMeO Hf YHO Gddg Hf EOQjS GdMSfj GdWGdHj, CHh YHO Gddg,J (B560 (3g` s
(3ChdgG (B:s
(3Ef gPG GdEbdje GdChd eHOhg ef Lgg GdeZQH ef GdHMQ GdZQHi s
(3BNQgG (B:s
(3hLejY fHGJ gPG GdLHd EfeG ghfHGJ GdHbe hjNQL Edi SGjQ GdCbWGQ s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B236s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1947s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3LZQGajG (B731) s
Keywords: (3GdLZQGajG h GdHdOGfs